Development of Feeling Board Media to Stimulate Social-Emotional Development in Children Aged 5-6 Years - Ulfah Nur’afifah; Muhammad Saepul Ulum (Edu Happiness: Jurnal Ilmiah Perkembangan Anak Usia Dini, 2026)
This study aims to develop and evaluate the effectiveness of the Feeling Board media as an instrument to stimulate the social-emotional development of children at PAUD Al-Huda. This research was motivated by field observations indicating that children still experienced difficulties in identifying personal emotions, regulating themselves, and engaging in peer cooperation. This study employed a Research and Development (R&D) approach adapted from the Borg and Gall model, consisting of six stages: data collection, planning, product development, preliminary testing, revision, and field testing. Data were collected through observation, interviews, documentation, and developmental assessments involving 10 children aged 5–6 years. The results of material expert validation showed an average score of 4.1 (categorized as good), indicating that the media is feasible for implementation. Furthermore, field testing demonstrated a significant improvement in children’s social-emotional competence, with all participants achieving the “Very Well Developed” (BSB) category and a success rate of 87%. These findings confirm that the Feeling Board media is an effective interactive tool for optimizing early childhood social-emotional development.